An Update of the International Society of Sexual Medicine's Guidelines for the Diagnosis and Treatment of Premature Ejaculation (PE). Issue 2 (1st June 2014) - Althof, Stanley E.; McMahon, Chris G.; Waldinger, Marcel D.; Serefoglu, Ege Can; Shindel, Alan W.; Adaikan, P. Ganesan; Becher, Edgardo; Dean, John; Giuliano, Francois; Hellstrom, Wayne J.G.; Giraldi, Annamaria; Glina, Sidney; et al.
Abstract: Introduction: In 2009, the International Society for Sexual Medicine (ISSM) convened a select panel of experts to develop an evidence-based set of guidelines for patients suffering from lifelong premature ejaculation (PE). That document reviewed definitions, etiology, impact on the patient and partner, assessment, and pharmacological, psychological, and combined treatments. It concluded by recognizing the continually evolving nature of clinical research and recommended a subsequent guideline review and revision every fourth year. Consistent with that recommendation, the ISSM organized a second multidisciplinary panel of experts in April 2013, which met for 2 days in Bangalore, India. This manuscript updates the previous guidelines and reports on the recommendations of the panel of experts. Aim: The aim of this study was to develop clearly worded, practical, evidenced-based recommendations for the diagnosis and treatment of PE for family practice clinicians as well as sexual medicine experts. Method: A comprehensive literature review was performed. Results: This article contains the report of the second ISSM PE Guidelines Committee. It offers a new unified definition of PE and updates the previous treatment recommendations. Brief assessment procedures are delineated, and validated diagnostic and treatment questionnaires are reviewed. Finally, the best practices treatment recommendations are presented to guide clinicians, both familiar and unfamiliar with PE, in facilitating treatment of their patients. Conclusion: Development of guidelines is an evolutionary process that continually reviews data and incorporates the best new research. We expect that ongoing research will lead to a more complete understanding of the pathophysiology as well as new efficacious and safe treatments for this sexual dysfunction. We again recommend that these guidelines be reevaluated and updated by the ISSM in 4 years.